PEMBUATAN SKENARIO FILM œLEGENDA TANJUNG MENANGIS DARI NASKAH LONTAR CILINAYA: SEBUAH PROSES EKRANISASI - Eva Mawinda Widiyastantia (Gorga : Jurnal Seni Rupa, 2024)
AbstractOn the island of Lombok, one of the renowned ancient manuscripts both in presence and legend is the Cilinaya palm-leaf manuscript. Historically, the ancient lontar Cilinaya manuscript has only been kept in museums and held by traditional leaders to be read occasionally during cultural processions. This research deliberately made the script into a film scenario as a form of revitalization and cultural preservation that has the potential to continue to be developed. The objective of this endeavor is to create the film screenplay " Legenda Tanjung Menangis," an adaptation of the ancient Cilinaya palm-leaf manuscript. The findings of this research indicate the feasibility of adapting the ancient Cilinaya palm-leaf manuscript from Lombok into a film screenplay. The process of adaptation involves three primary stages: transcription, translation, and transcreation. Transcription, as the initial phase, encompasses the conversion of the original script written in the traditional script into Latin script. Subsequently, the translation phase involves the transliteration of the original text from the Sasak language of the palm-leaf manuscript into Indonesian. Following this, the transliterated text serves as the foundation for crafting a film screenplay, necessitating a transcreation process to adapt the text into a visual format suitable for the film medium. After undergoing these three stages, the ancient palm-leaf manuscript has successfully been adapted into the film screenplay "Legenda Tanjung Menangis".Keywords: Ancient Manuscript, Cilinaya Lontar, Ecranisation, LegendAbstrakDi Pulau Lombok, salah satu naskah lontar yang terkenal keberadaan dan legendanya adalah lontar Cilinaya. Selama ini naskah kuno lontar Cilinaya hanya tersimpan di museum dan dipegang oleh pemangku adat untuk sesekali dibacakan pada prosesi kebudayaan. Penelitian ini dengan sengaja membuat naskah tersebut menjadi skenario film sebagai bentuk revitalisasi dan pelestarian budaya yang berpotensi untuk terus dikembangkan. Tujuan penciptaan ini adalah menciptakan skenario film œLegenda Tanjung Menangis yang merupakan ekranisasi dari naskah kuno lontar Cilinaya. Temuan penelitian ini menunjukkan bahwa naskah kuno lontar Cilinaya yang berasal dari Pulau Lombok dapat diekranisasi menjadi sebuah skenario film. Proses ekranisasi melibatkan tiga langkah utama, yakni alih aksara, alih bahasa, dan alih wahana. Alih aksara merupakan langkah pertama yang melibatkan konversi tulisan asli dalam aksara jejawan menjadi aksara latin. Langkah berikutnya adalah alih bahasa, yang melibatkan transliterasi teks asli dari bahasa lontar Sasak ke dalam bahasa Indonesia. Setelah itu, hasil transliterasi tersebut dijadikan bahan dasar untuk menyusun sebuah skenario film yang sesuai, yang memerlukan proses alih wahana untuk mengadaptasi teks ke dalam format visual yang sesuai dengan medium film. Setelah melewati tiga tahap tersebut, naskah kuno lontar telah berhasil diekranisasi menjadi skenario film œLegenda Tanjung Menangis.Kata Kunci: Naskah kuno, Lontar Cilinaya, Ekranisasi, Legenda Author:Eva Mawinda Widiyastantia: Institut Seni Indonesia YogyakartaReferences:Buda, I. K., Payuyasa, I. Nyoman, & Chrisna, I. M. D. (2020). Pendidikan yang memerdekakan dalam film œSokola Rimba. Gorga: Jurnal Seni Rupa, 09(02), Juli-Desember 2020. DOI: 10.24114/gr.v9i2.19823Cahir, L. C. (2006). Literature into Film: Theory and Practical Approaches. North Carolina: McFarland.Desmond, J. (2006). Adaptation: Studying Film and Literature. New York: McGraw-Hill Education.Field, S. (2005). Screenplay: The Foundations of Screenwriting. London: Delta.Herman, R. (2017). Ekranisasi, Sebuah Model Pengembangan Karya Sastra. CEUDAH Jurnal Ilmiah Kesusastraan, 7(1). https://susastra.hiski.or.id/jurnal/index.php/susastra/article/view/42Oktafiyani, A., Suseno, A., & Nuryati. (2017). Transformasi Makna Simbolik Mihrab pada Novel ke Film dalam Mihrab Cinta Karya Habiburrahman El Shirazy: Kajian Ekranisasi. Jurnal Sastra Indonesia, 6(3). https://journal.unnes.ac.id/sju/jsi/issue/view/1242Permadi, T. (2017). Naskah Nusantara dan Berbagai Aspek yang Menyertainya. Diakses dari http://file.upi.edu/Direktori/FPBS/JUR._PEND._BHS._DAN_SASTRA_INDONESIA, 1“33.Primadesi, Y. (2012). Peran Masyarakat Lokal dalam Usaha Pelestarian Naskah-Naskah Kuno Paseban. Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 11(2). DOI:  10.24036/komposisi.v11i2.88Suwaji, I. G. M. G. (2011). Lontar, Katalog Induk Naskah Koleksi Bali. Bali: Dinas Kebudayaan Provinsi Bali.Seger, L. (2009). The Art of Adaptation: Turning Fact and Fiction into Film. London: Routledge.